Extralinguistic Means Of Expressing Appeal In The Uzbek Language - Zukhro Akmaljonovna Akbarova; Vasilakhon Avazkhon qizi Giyosova (Zien Journals, 2023)
In this article, the appearance of words such as hand, eye, eyebrow, eyelid, face, lip as an extralinguistic tool in the process of addressing is highlighted on the basis of examples.
Keywords: address form; extralinguistic tool; language system; speaker